The Sage handbook of nature three volume set - Marsden, Terry (SAGE Inc., 2018)
The SAGE Handbook of Nature offers an ambitious retrospective and prospective overview of the field that aims to position Nature, the environment and natural processes, at the heart of interdisciplinary social sciences. The three volumes are divided into the following parts: INTRODUCTION TO THE HANDBOOK NATURAL AND SOCIO-NATURAL VULNERABILITIES: INTERWEAVING THE NATURAL & SOCIAL SCIENCES SPACING NATURES: SUSTAINABLE PLACE MAKING AND ADAPTATION COUPLED AND (DE-COUPLED) SOCIO-ECOLOGICAL SYSTEMS RISK AND THE ENVIRONMENT: SOCIAL THEORIES, PUBLIC UNDERSTANDINGS, & THE SCIENCE-POLICY INTERFACE HUNGRY AND THIRSTY CITIES AND THEIR REGIONS CRITICAL CONSUMERISM AND ITS MANUFACTURED NATURES GENDERED NATURES AND ECO-FEMINISM REPRODUCTIVE NATURES: PLANTS, ANIMALS AND PEOPLE NATURE, CLASS AND SOCIAL INEQUALITY BIO-SENSITIVITY & THE ECOLOGIES OF HEALTH THE RESOURCE NEXUS AND ITS RELEVANCE SUSTAINABLE URBAN COMMUNITIES RURAL NATURES AND ..
Keywords: Nature -- Handbooks, manuals, etc; Nachhaltigkeit; Gesellschaft; Natur; Umweltschutz; Ökologie; Umweltethik